EFFECT OF EDUCATIONALINTERVENTIONS ON ONCOLOGY NURSE KNOWLEDGE AND PRACTICE ABOUT THE CARE OF CHEMOTHERAPY PATIENTS WITH PORT-A- CATHETER (Journal of Medical & Health Sciences Review, 2025)
Background: Cancer is a proliferative, invasive, and metastatic disease that is caused by an accumulation of genetic abnormalities that randomly produce a malignant cell. Chemotherapy is the most commonly prescribed cancer treatment modality, which utilizes chemical agents or drugs that destroy cancer cells in the cell cycle and inhibit the growth and spread of cancerous cells. It may be combined with surgery or radiation therapy, or both to reduce tumor size preoperatively and to destroy remaining tumor cell postoperatively. Oncology nurses play a pivotal role in caring of Port-A-Catheter, being responsible for maintaining access integrity, preventing its failure and reducing access related complications.Objective: To assess the effect of Educational Interventions on Oncology Nurse Knowledge regarding the Care of Chemotherapy Patients with Port-A- Catheter.Methods: A quasi-experimental study design was used. The study setting and adulation participants were taken from inpatient oncology department of NIMRA Cancer Hospital, LUMHS Jamshoro, and Karachi, Pakistan. Purposive sampling and time duration was 9 months. The calculated sample Size was less than 30. So 30 participants was taken after Adding 20% drop out rate the sample size was 36. The both male and female have age between 23-45  with six month experience in chemotherapy were selected for this research.Results: After the intervention, nurses showed a significant improvement in both knowledge and practices related to port-a-cath care. The average knowledge score increased markedly from pre-intervention (M = 0.3611, SD = 0.1381) to post-intervention (t = 15.687, p < 0.001). Similarly, practical skills improved significantly (M = 0.3968, SD = 0.1920; t = 12.401, p < 0.001). Post-test correct responses exceeded 70% on most items, with over 83.3% correctly identifying key aspects such as port placement, disinfectants, and complications. Clinical compliance with procedures like flushing, dressing, and documentation also rose above 75%. These findings confirm that the intervention had a statistically significant positive impact on nurses' competency in managing port-a-cath.Conclusion: This study underscores the vital role of education in enhancing oncology nurses' knowledge and practices related to Port-A-Catheter care. Initially, significant knowledge gaps in infection control, complication management, and maintenance were identified. Following a structured educational program, nurses demonstrated marked improvement in both understanding and clinical application.